FILSAFAT ANALITIS BAHASA DAN HUBUNGANNYA DENGAN ILMU LINGUISTIK PRAGMATIK - Sunardi Sunardi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2011)
The development of pragmatic linguistics cannot be separated from the development of analytic philosophical tradition which focuses on ordinary language. Analytic philosophy falls into three main branches: logical atomism, logical positivism, and ordinary language philosophy. According to the philosophy of logical atomism, a reality is expressed in language propositions, not ideas. A proposition is everything which can be verified to be true or false. Meanwhile, logical positivism philosophy is characterised by positive evaluation of knowledge and scientific method. Unlike logical atomism and logical positivism, ordinary language philosophy does not base on language logic, but on the ordinary language which human beings use in their daily activities. In thisordinary language philosophy, language is studied from both structural and functional aspects. Language is studied from its fundamental function in daily life. This idea of language philosophy inspired the development of pragmatic linguistics. Some language philosophers, such as Austin, Searl, and Grice, initiated the development of pragmatic linguistics through their ideas on speechacts and cooperative principle.Keywords: logical atomism, logical positivism, ordinary language philosophy,pragmatic linguistics